Anesthesia management of a parturient with meningioma underwent elective c-section - Chandra, Susilo (Bali Journal of Anesthesiology, 2019)
ABSTRACTThe occurrence of primary intracranial tumors in pregnancy is an extremely rare event. Symptoms of a brain tumor include nausea, vomiting, headache, visual disturbances and seizures which mimic symptoms of pregnancy-related hyperemesis or eclampsia. It is a well-established fact today that the technique of choice for elective cesarean section is regional anesthesia. However, in patients with intracranial hypertension and central nervous system infection, this technique should be avoided. General anesthesia poses high risks for pregnant patients. These patients have potentially difficult airways with delayed gastric emptying, which are factors increasing the possibility of pulmonary aspiration after general anesthetic induction. This paper aimed at reporting the anesthetic management of a parturient with intracranial hypertension due to meningioma submitted to elective cesarean section. This kind of surgery needs special attention and specific skill of the anesthesiologist.